Scenario, implications and prospects of climate change on potato (Solanum tuberosum) insect pests: A review - BHATNAGAR, ANUJ; DUA, V K; CHAKRAWARTI, S K (The Indian Journal of Agricultural Sciences, 2018)
Potato (Solanum tuberosum L.) is a cool climate loving crop. Climatically, there is a short window in which potato has been fitted with appreciable use realized even 80 to 90 days old crop. Moreover a few other crops produce comparatively high yields of nutrients per unit area where land is scarce. Thatâ€™s why potatoes are highly important formany marginal families of the country. High production levels and highly perishable sale practices enable farmers to be competitive despite the fact of high input cost, labour problem and forced gluts, still potato is an important cash crop and cultivated mainly as an irrigated winter cash crop. Among the various factors related to insect pestsand diseases, potato farmers are increasingly forced to face water stress change, changes in rainfall patterns and its intensity, frost and fog etc. These conditions are generally interpreted to be climate changes. Potato productionis highly dependent on climate and weather factors. All climate change projections are based on simulations andtherefore involve uncertainties. However, it is clear that climate change will not only affect the cultivation system butalso change the pressure of insect pests of potato. Disease free seed production may also be affected due to changesÂ in the life cycles of aphids. Pests such as mite, potato tuber moth and cutworms may become more serious on potatocrop. At present most of the potato seed is grown in Northern plains under no or low aphid period in order to keep it virus free but change in climate, in certain regions, aphids/whiteflies will occurs in greater numbers, resulting threat particularly to virus free seed production. The precise impact of climate change on insects is somewhat uncertain because some changes may favours insects while other may inhibit the activity of few insects. The best economic strategy for farmers is to use IPM practices to monitor insect occurrence and their buildup on potato crop.